2017
DOI: 10.11648/j.ajlm.20170205.13
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Enteric Bacteria from Hawked “Kunun-Zaki” in Chikun Local Government Area of Kaduna State

Abstract: Two hundred samples of freshly formulated Kunun-zaki, a locally fermented non-alcoholic cereal beverages were obtained from local hawkers in five (5) different locations in Chikun Local Government of Kaduna State, Nigeria and screened for enteric bacteria. They were analyzed using the Spread Plate Method. The pH of the samples ranged between 3.00 -7.50 and total bacterial count ranged between 2.0 × 10 4 -9.0×10 5 cfu/ml. The microorganisms recovered were Esherichia coli, Proteus vulgaris, Proteus mirabilis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some studies carried out on the product in Nigeria [83][84][85][86][87][88][89][90][91][92] show that the beverage has serious hygiene concerns because the prevalence of Escherichia species was highest in this product when compared to others reviewed (Table 1). A comparison between freshly processed and street-hawked kunu [86] showed that the fresh samples were free of coliforms whereas products found on the street were not.…”
Section: Kunumentioning
confidence: 99%
“…Some studies carried out on the product in Nigeria [83][84][85][86][87][88][89][90][91][92] show that the beverage has serious hygiene concerns because the prevalence of Escherichia species was highest in this product when compared to others reviewed (Table 1). A comparison between freshly processed and street-hawked kunu [86] showed that the fresh samples were free of coliforms whereas products found on the street were not.…”
Section: Kunumentioning
confidence: 99%